2021
DOI: 10.1038/s41386-021-00955-1
|View full text |Cite
|
Sign up to set email alerts
|

Restoring glutamate homeostasis in the nucleus accumbens via endocannabinoid-mimetic drug prevents relapse to cocaine seeking behavior in rats

Abstract: Impaired glutamate homeostasis is a key characteristic of the neurobiology of drug addiction in rodent models and contributes to the vulnerability to relapse to drug seeking. Although disrupted astrocytic and presynaptic regulation of glutamate release has been considered to constitute with impaired glutamate homeostasis in rodent model of drug relapse, the involvement of endocannabinoids (eCBs) in this neurobiological process has remained largely unknown. Here, using cocaine self-administration in rats, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 101 publications
0
36
0
Order By: Relevance
“…In fact, the neuronal origin of basal extracellular glutamate regulated by CB1R is supported by the previous observation that administration of AM251 alone induced an increase of extracellular glutamate in NA in a TTX-dependent manner 18 . It should be noted that after chronic perfusion of methAEA, a partial agonist of CB1R with a more robust effect on astrocytic CB1R than on presynaptic CB1R, restored the impaired glutamate homeostasis in cocaine-experienced rats, and subsequently prevented reinstatement 75 . This latter mechanism can be proposed as an alternative or indirect pathway to obtain similar results to that proposed for the acute administration of AM251 18 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, the neuronal origin of basal extracellular glutamate regulated by CB1R is supported by the previous observation that administration of AM251 alone induced an increase of extracellular glutamate in NA in a TTX-dependent manner 18 . It should be noted that after chronic perfusion of methAEA, a partial agonist of CB1R with a more robust effect on astrocytic CB1R than on presynaptic CB1R, restored the impaired glutamate homeostasis in cocaine-experienced rats, and subsequently prevented reinstatement 75 . This latter mechanism can be proposed as an alternative or indirect pathway to obtain similar results to that proposed for the acute administration of AM251 18 .…”
Section: Discussionmentioning
confidence: 97%
“…A third hypothesis can be related to the activity of CB1R expressed in astrocytes 75 , 76 . A recent work, using NA slice electrophysiology from cocaine-experienced rats, showed that activation of CB1R causes an excitatory event that typically corresponds to astrocytic glutamate release 75 . However, this mechanism seems not to impact significantly on those in vivo changes in extracellular glutamate detected during the perfusion of ACEA in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not evaluated synaptic NMDA receptors signalling or SICs at long withdrawal intervals, but a number of recent studies indicate that cocaine‐induced increase in extrasynaptic NMDA signalling may be a transient phenomenon. For example, initial upregulation of extrasynaptic NMDA receptors was found to dissipate by 1 month of withdrawal from cocaine 76 and 14 days of extinction training was not associated with differences in SIC frequency in the NAc 81 . Relative abundance of extrasynaptic NMDA receptors may also be synergistic with the effects of dendritic sprouting reported after cocaine because dendritic coverage has been shown to influence duration of synaptic transients 82,83 .…”
Section: Discussionmentioning
confidence: 99%
“…PEA- and OEA-mediated inhibition of astrocyte activation seems to involve PPAR-α [ 161 , 162 ]. Furthermore, AEA has been shown to elicit glutamate release through astrocytic CB 1 receptor activation in the core of nucleus accumbens in rats [ 163 ].…”
Section: Neuroinflammation-induced Synaptopathy and Neurodegenerative Diseasesmentioning
confidence: 99%